Ethnoveterinary remedies used in the Algerian steppe: Exploring the relationship with traditional human herbal medicine. (15th November 2019) - Miara, Mohamed Djamel; Bendif, Hamdi; Ouabed, Asmahane; Rebbas, Khellaf; Ait Hammou, Mohammed; Amirat, Mokhtar; Greene, Alex; Teixidor-Toneu, Irene
Abstract: Ethnopharmacological relevance: Ethnoveterinary medicine is vastly under-documented, especially in North Africa, where livestock care is increasingly medicalised. Despite evidence of the interdependence of ethnoveterinary practices and ethnomedicine for human care, the overlap between these two systems and the possible drivers of similarity are rarely addressed in ethnopharmacological literature. Here, we present the first quantitative comparison of remedies used to treat human and animal health among a pastoral society. Aims: This study aims to document the plants and other materials used in ethnoveterinary medicine among nomadic herders in the Algerian steppe. We calculate the overlap with remedies used for human health and evaluate some of the possible drivers of similarities between the two interlinked medical systems. Methods: The field study was conducted in spring 2018 with 201 local knowledge holders in five provinces in the central part of the Algerian steppe. Forty-six camps and ten weekly animal markets were visited. After obtaining prior informed consent, data was collected through structured interviews. Anonymous sociodemographic information was collected along with veterinary use data. Plant specimens were acquired, identified and deposited in the Botanical Laboratory Herbarium of the University of Tiaret. Ethnobotanical information was structured in use reports and therapeutic applications organised into 13 simple categories. Plants used in ethnoveterinary medicine were compared to those used in human health care using a Chi square test, and ethnoveterinary use was predicted using a generalised linear model with use for human care and plant family as predictive variables. Logistic regressions were also used to test if any specific medicinal application predicts shared use in human and veterinary medicine. Results: Sixty-six plant species from 32 botanical families and ten non-vegetable remedies were documented. Plants from the Lamiaceae, Asteraceae, Fabaceae and Apiaceae families were most commonly used. The plants most often cited by interviewees are all harvested from the wild ( Echinops spinosissimus Turra, Atriplex halimus L., Artemisia campestris L., Juniperus phoenicea L. and Peganum harmala L.). Leaves are the most commonly used plant part and decoction is the most common preparation method. There are important similarities between remedies used to treat humans and other animals: two thirds of the remedies used in ethnoveterinary medicine are also used in human health care, and these represent half of the human health treatments. Use for human health and plant family both predict the use of a medicinal plant in veterinary medicine, but no correlation is found regarding specific therapeutic applications. Conclusions: Traditional veterinary knowledge is still key to sheep and goat herders in the Algerian steppe, but a knowledge transmission gap seems to exist between older and younger generations, and ethnoveterinary practices may disappear in the near future. Treatments for human and animal care overlap to a large extent, and a causal relationship possibly exists for, at least, some of them. However, overall a smaller number of remedies are used to treat animals than humans and for less therapeutic applications. This difference in the diversity of therapeutic applications and remedies should be the object of future research. Graphical abstract: Image 1